Tafsir Ayat-Ayat Tentang Konsumsi (Aplikasi Tafsir Ekonomi al-Qur'an) - Lukman Fauroni (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2008)
This essay tries to develop economic studies from the point of view of Quranic economic tafsir. As a methodology, tafsir plays significant role in order to develop Islamic economic discipline. This model of economic tafsir derived from the thematic Quranic interpretation is developed through four phases including; classification of Quranic verses pertinent to economic affairs, understanding them based on chronology, micro and macro context, and socio-economic contextualization. To sum up, this paper reveals that the consumption behavior in the Quran is ruled harmoniously, gradually and systematically in order to propose the new model of consumption for the Muslim community through eight axiomatic Islamic consumption behavior. Keyword: economic tafsir al-Qur'an, adabi al-Ijtima'i wal iqtishadfyyah, consumer behaviour, axiomatic Islamic consumption behavior